1999
DOI: 10.2115/fiber.55.10_464
|View full text |Cite
|
Sign up to set email alerts
|

Flammability Measurement and Thermal Aging of Chemical Protective Suit Materials.

Abstract: Test methods were described for measuring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Tear strength was also assessed since it has been reported to be more sensitive to heat aging than tensile strength in a study involving various laminate‐type fabrics 14. A sample similar to the ASTM D 5587 standard test method15 but with slightly scaled‐down dimensions was used.…”
Section: Methodsmentioning
confidence: 99%
“…Tear strength was also assessed since it has been reported to be more sensitive to heat aging than tensile strength in a study involving various laminate‐type fabrics 14. A sample similar to the ASTM D 5587 standard test method15 but with slightly scaled‐down dimensions was used.…”
Section: Methodsmentioning
confidence: 99%
“…11 Tensile strength is a common index to represent the mechanical properties of fabrics. 12 An 13 pointed out that when fabric was exposed to both convection and conduction heat sources, the latter reduced the tensile strength of the fabric even less. Rossi et al 14 showed that when the heat flux was the same, the effect of convective heat exposure on the tensile strength was greater than that of radiant heat exposure.…”
mentioning
confidence: 99%
“…11 Tensile strength is a common index to represent the mechanical properties of fabrics. 12 An 13 pointed out that when fabric was exposed to both convection and conduction heat sources, the latter reduced the tensile strength of the fabric even less. Rossi et al.…”
mentioning
confidence: 99%